Waste Reduction Based on Adsorption Aqueous Lead Nitrate by Chicken Feather - Dhaningtyas, Shalihat Afifah (PROSIDING SEMINAR KESEHATAN MASYARAKAT, 2024)
Background: Chicken feathers can be used as an alternative treatment for metal ions in wastewater with a concentration of lead nitrate. This paper will describe the ability of chicken feathers that were activated by only Sodium hydroxide and by Sodium hydroxide with Hydrochloric acid based on some variation of the weight of chicken feathers to reduce the concentration of lead nitrate and subsequently, characterizing the spectral outcomes. Method: A quasi-experimental research with pre-test post-tests equivalent control groups design will be done. The purposive sampling consists of aqueous Pb(NO3)2 and chicken feathers are used. The 5 mg/L Pb solution was made from Pb(NO3)2 whose levels had been tested with AAS and were detected at 4.183 mg/L. Variations in chicken feather mass of 1.4 grams; 1.5 grams; 1.6 grams; and 1.7 grams were tested. Result: Based on the activation treatment, chicken feathers with a weight of 1.7 grams activated by sodium hydroxide have the highest ability to adsorb aqueous lead nitrate. The spectra match the functional groups of keratin. Conclusion: Activation using sodium hydroxide has reached a high adsorption presentation capacity. The spectral results match the functional groups of keratin C-H, C-O, N-H2 groups.